Perubahan Iklim: Tinjauan Holistik Sektor Batubara : Perubahan Iklim: Tinjauan Holistik Sektor Batubara - Ming Shen (PARAHYANGAN ECONOMIC DEVELOPMENT REVIEW, 2022)
The use of coal has increased due to the increasing use of electricity for human activities. On the other hand, action is needed to prevent the adverse effects of coal, namely greenhouse gas (GHG) emissions which result in increasingly warmer temperatures and cause climate change. This study aims to describe the advantages and disadvantages of using coal as the main energy resource. Because coal isn’t environmental-friendly, actions that can be taken to prevent climate change or reduce GHG emissions are to mitigate the energy sector by using new, renewable energy. Meanwhile, using new renewable energy sources is still accompanied by several challenges, so coal cannot replace the efficiency and effectiveness of coal as an energy resource. In the end, the transition from fossil energy to environmentally friendly energy is a long process achieved through the right direction of development plans and support from all parties.